2019
DOI: 10.1108/ijchm-05-2018-0380
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of lean-green practices on the sustainable performance of hotel supply chains

Abstract: Purpose The purpose of this paper is to empirically assess the impact of integrated lean and green practices on the sustainable (environmental, economic and social) performance of a hotel supply chain. Design/methodology/approach Literature review and previous exploratory studies were used to develop a hypothesized model that characterizes the integrated lean and green (LeGreen) impact on supply chain sustainability. A case study of a large sample of the UAE hotels is used to collect and analyze empirical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
101
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 51 publications
9
101
1
Order By: Relevance
“…The green environment and equipment dimension includes three factors: green kitchen environment, green dining environment, and green cleaning and post-treatment (Wang et al, 2013). Some studies (e.g., Hussain et al, 2019) showed that applying more efficient water and energy consumption and waste recycling methods subsequently reduces overall operational costs.…”
Section: Green Restaurantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The green environment and equipment dimension includes three factors: green kitchen environment, green dining environment, and green cleaning and post-treatment (Wang et al, 2013). Some studies (e.g., Hussain et al, 2019) showed that applying more efficient water and energy consumption and waste recycling methods subsequently reduces overall operational costs.…”
Section: Green Restaurantsmentioning
confidence: 99%
“…There are certain benefits of adopting green practices in the food-service industry. These benefits include increased customers' purchasing intentions to pay more for green products (DiPietro et al, 2013;Namkung and Jang, 2017); increased customer satisfaction and loyalty (Barber and Deale, 2014); improved employee satisfaction and loyalty (Alcorn, 2014;Chiu and Hsieh, 2016); reduced operating costs (Chiu and Hsieh, 2016;Schubert et al, 2010); improved image and customer satisfaction (Chiu and Hsieh, 2016;Hu et al, 2010); enhanced competitiveness (Chiu and Hsieh, 2016;Schubert et al, 2010); and improved environmental and financial performance (Chiu and Hsieh, 2016;Hussain et al, 2019;Perramon et al, 2014). However, some barriers prevent the food-service industry from adopting green practices: high costs related to implementing environmental technologies (Chan, 2011), lack of social awareness and green education (Abbas and Hussien, 2017), lack of resources, lack of support, and uncertainty of outcomes (Chan, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Global Sustainable Tourism Council (GSTC) in alliance with International Social and Environmental Accreditation and Labeling Alliance (ISEAL) are organized around four themes for hotels' sustainable practices: "effective sustainability planning, maximizing social and economic benefits for the local community, enhancing cultural heritage, and reducing negative impacts to the environment" [38] (p. 1). Similar to manufacturing firms, green adoption in hotels that provide services is increasingly accepted as indispensable to generating long-term profitable services that positively reflect on the firms' environmental and social responsibilities [81]. Furthermore, Saura et al [82] explored that hotels' environmental practices should expand beyond the physical location of the hotel, rather they should extend to the surrounding environment "including the pure air in the facilities and surroundings, the absence of noise, and the abundance of nature and plants, in the hotel ecosystem" (p. 14).…”
Section: Green Hotels and Sustainable Practicementioning
confidence: 99%
“…To satisfy the consumers, hotels are obliged to focus on building their image as "green hotel" in line with sustainable practice. In a "survey conducted by TripAdvisor, it was revealed that about 62.0% of travelers are concerned about the environmental issue when deciding to stay at a hotel [81]; nearly 87.0% of guests are aware of the importance of eco-friendly hotel, about 80.0% of guests consider themselves as eco-conscious customers, and about 30.0% of them are willing to pay more for environmentally responsible hotels" [84] (p. 58).…”
Section: Green Hotels and Sustainable Practicementioning
confidence: 99%